Brincar-brinquedo, criar-fazendo: entrelaçando pluriversos de infâncias e crianças desde o sul de Moçambique - Pastore, Marina Di Napoli (2020)
Based on the understanding of children as sociocultural beings and active agents in the productions of the world around them, this study aims productions of the world around them, the present work aims to understand the play and the relationships that precede, mediate and succeed them, as a meaningful activity of children and possibility of transformations and rereading of possible worlds, from three Mozambican communities located in the south of the country. The longitudinal fieldwork carried out from 2014 to 2018 covered three main data collection periods: six months during 2014, 2017 and 2018 in the communities of Mabotine (urban area of the capital of Maputo ), Matola A (peri-urban area of the city of Matola) and Nhandlovo (rural area in the city of Massinga, Inhambane), with children aged 3 years to 17 years. The places where the ethnographic research happened permeated the places where the children were, especially those in the community, such as the streets, the backyards, the “secret” spaces, the river, the houses, the schools, among others considered significant for them. With the ethnography, other methods have also been employed in seeking a greater understanding of play: photography, drawing, video, unstructured interviews, semi-structured interviews, and informal conversations. From the data collected and analyzed, four main points were worked on: the idea of being a child from the perspective of children and adults themselves; the playing and construction of toys from discarding material; play and the relationship with nature and landscapes; images of play and the use of photography. The aspect is brought, analyzed and discussed in chapters that follow the present thesis, considering its relationship with occupational therapy, its practices and theories. The results point to a kaleidoscope of diversity and language used by children in play, understood as a way of being in the world and from their spatiotemporal relations. Finally, questions are raised about the potentialities of future development in African and childhood studies, pointing to the coexistence of childhood and child pluriverses, as well as possible research methods.